2003
DOI: 10.1002/sia.1576
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of quantification in r.f. GDOES

Abstract: Quantification algorithms for radiofrequency glow discharge optical emission spectroscopy (r.f. GDOES) calibration and analysis are briefly reviewed. These include corrections for emission yield, self-absorption, spectral interferences and relative sputtering rates. The emission yield term is then expanded to allow variable power calibration. The use of sputter factors to determine relative sputtering rates is explored. Finally, pulsed r.f. operation is considered and compared with continuous power operation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…It is an atom‐dependent and instrument‐dependent parameter, which must be determined independently for each spectral emission line and instrument. The different approaches developed so far to obtain quantitative compositional depth profiling are based on the assumption that the emission yield in GDs is essentially a matrix‐independent quantity .…”
Section: Resultsmentioning
confidence: 99%
“…It is an atom‐dependent and instrument‐dependent parameter, which must be determined independently for each spectral emission line and instrument. The different approaches developed so far to obtain quantitative compositional depth profiling are based on the assumption that the emission yield in GDs is essentially a matrix‐independent quantity .…”
Section: Resultsmentioning
confidence: 99%
“…This does not imply that this information is totally lost. On the contrary, recent rf-GD-OES studies by Payling and co-workers have shown that accurate information can be obtained from the first 2 nm of metallic specimens [43].…”
Section: Profiling Of a Boron-implanted Silicon Wafermentioning
confidence: 97%
“…Concentration profiles in the direction normal to the coating surface were measured by glow-discharge optical emission spectroscopy (GD-OES) using a JY 5000 RF instrument from Jobin-Yvon Horiba and equipped by a glow-discharge source of 4 mm diameter [14].…”
Section: Methodsmentioning
confidence: 99%